Single point positioning using low cost single frequency GPS receiver - Mondali, Mondali (2005)
Since the Selective Availability (SA) was set to zero, the point positioning becomes an interesting field of study. This study was to develop the single point position solution with accuracy better than 2 m using a low cost single frequency GPS receiver. The positioning algorithm was written in MatlabTM and it incorporates all the significant errors and bias. The significant errors and bias are satellite clock errors, receiver clock errors, tropospheric and ionospheric bias, relativistic effect, earth rotation effect, and satellite antenna phase center offset. Some simulations were performed to validate the result. The results of the study showed significant improvements in accuracy after the SA was set to zero and this fits to the statement of the White House USA that the accuracy will be ten times better than before. Using a low cost single frequency GPS receiver and self algorithm written in MatlabTM, it could be seen that most of the position accuracy could be better than 5 m for horizontal and 10 m for vertical. The 2 m accuracy level in some epochs could be reached. The findings suggest that it could be enhanced for better accuracy and integrated in a single built system of hardware and software for further and higher investigations as a low cost commercial GPS equipment.